Konstruksi Pemberitaan Kasus Perselingkuhan Nissa Sabyan dan Ayus Sabyan di Tribunnews.com - Wahyu Kristian Natalia; Ahmad Khairul Nuzuli (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2022)
In February 2021, the public was shocked by the case of an affair involving Nissa Sabyan and Ayus Sabyan. One of the media that gave the most in this case was Tribunnews.com. This study aims to see how Tribunnews.com's news construction is in the case of Nissa Sabyan and Ayus Sabyan's infidelity. Gender sensitive journalism and the framing process in reporting are the basis of this research. The research model uses framing analysis by Robert N. Entman. The results of the study show that Tribunnews.com strengthens the labeling of pelakor to Nissa Sabyan. The labeling of actors positions women as the most guilty parties in infidelity cases. This shows that Tribunnews.com has discriminated against gender in reporting.